The right kind of suffering: gender, sexuality, and Arab asylum seekers in America - Kanaaneh, Rhoda Ann (University of Texas Press, 2023)
"Even before the former administration upended the asylum process in the US, it was an exacting and drawn-out process that turned away many people. Overloaded courts, constantly changing dates and appointments, and the need to prove oneself the "right" kind of asylum seeker were harrowing enough before adding the language barrier that many faced. Rhoda Kanaaneh became a volunteer translator for Arab plaintiffs and soon began to learn the ins and outs of the system by hearing the lawyers of those who were lucky enough to have them explain how the process worked to their clients. In this book, she follows the cases of four Arabs who sought asylum on the grounds of their gender or sexuality and how they had to demonstrate "the right kind of suffering" for the courts. Suad had to make sense of her confused memories in order to present an ordered story of her forced circumcision and police harassment in Sudan. Fatima had to visit doctors and therapists to document decades of abuse at the hands of her husband, while downplaying the resultant mental illness she suffered. Fadi had to look "gay enough" to qualify for asylum even after documenting his arrest and torture in Jordan because of his homosexuality. Marwa had to downplay her environmental activism while explaining her hardship as a lesbian in a Shiite family in Lebanon. All four of these asylum seekers were ultimately successful after many years, thanks to the help of pro-bono lawyers who taught them how to navigate the system and highlight certain aspects of their lives while hiding others in order to strike the right note for the courts. Kanaaneh uses their stories to open the door to the painful process of asylum, where more fail than succeed. She also describes the unique challenges Arab asylum seekers faced in the post-9/11 United States and what their travails revealed about the country in which they wanted to find refuge"--